(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): The organisation aims to achieve lean production through a system of continuous improvement, with the objective of eliminating waste in all areas of work. What technological times can bring us. Purpose: The purpose of the study is to investigate the impact of technological lead times in the production process. The aim is to identify and analyse the importance of lead times and their impact on various factors such as: planning, employee evaluation based on the achievement of lead time norms in relation to employee satisfaction, and product pricing. The survey should confirm to us the importance of appropriate technological timing. Method:Qualitative method with eight interviews. The employees interviewed work in different jobs and departments, so their work tasks are completely different. We also reviewed the professional and scientific literature, and applied research methods with analytical parsing to extract the essence and conclusions. Results: Our qualitative research has led us to certain conclusions. The interview questions were analysed and links between the answers were drawn. Using the analytical software tool Atlas. ti 8, we obtained a diagram of the links between the answers of the different respondents. Most of the questions were answered in the same way, thus confirming the theses. The exception was the question on improving employee satisfaction, where we got different opinions from respondents, so we did not confirm the thesis. The fact is that technology times are important for the production process. This is also clear from the selected literature. Organization: Adequate technological lead times and increased employee satisfaction are two factors that can have an impact on increasing productivity and, in turn, improving an organisation’s performance. This gives us greater opportunities to invest in technology that is greener and safer to work with. Society: This survey aims to highlight the importance of technology times in an organisation. The survey will certainly help to regulate technology times more accurately and more quickly. This can improve the planning of production processes, regulate product prices, increase employee satisfaction and, as a result, the organisation’s bottom line. Better business means better pay for the work you do. If we earn more, we can spend more. As consumption rises, so does supply, with a positive impact on society as a whole. Good business performance can also lead to more investment to make it greener and safer for people to work. Modern machinery also has an impact on occupational safety and reduces the chances of occupational diseases. The eventual improvement in operating results may lead to an increase in the volume of work, and thus the possibility of new jobs and the recruitment of local staff. Originality: The survey looks at the technological times. Based on interviews, it explains their meaning and impact. Limitations/Future Research: The survey is limited to one organisation. It would be interesting to investigate the impact of technology lead times on other factors such as inventory reduction, identification of bottlenecks in the company, investment needs, number of employees, increase in customer satisfaction due to possible shorter delivery times.